2021
DOI: 10.1021/acs.inorgchem.0c02668
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Bismuth or Bismuth Selenide Nanosheets from a Metal Organic Precursor: Investigation of their Catalytic Performance for Water Splitting

Abstract: The development of cost-effective, functional materials that can be efficiently used for sustainable energy generation is highly desirable. Herein, a new molecular precursor of bismuth (tris(selenobenzoato)bismuth(III), [Bi(SeOCPh) 3 ]), has been used to prepare selectively Bi or Bi 2 Se 3 nanosheets via a colloidal route by the judicious control of the reaction parameters. The Bi formation mechanism was investigated, and it was observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…Indeed, the high-resolution Bi 4f spectrum can be fitted with two doublets (Δ = 5.3 eV) whose more intense components are centered around 158.1 and 158.9 eV, respectively. The first contribution comes from bismuth bound to selenium (in the matrix) 39 and to sulfur (in MAA), while the second likely stems from surface oxidation (BiO x ). The Se 3d spectrum was also fitted with two doublets (Δ = 0.86 eV, the intensity ratio of 0.735).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, the high-resolution Bi 4f spectrum can be fitted with two doublets (Δ = 5.3 eV) whose more intense components are centered around 158.1 and 158.9 eV, respectively. The first contribution comes from bismuth bound to selenium (in the matrix) 39 and to sulfur (in MAA), while the second likely stems from surface oxidation (BiO x ). The Se 3d spectrum was also fitted with two doublets (Δ = 0.86 eV, the intensity ratio of 0.735).…”
Section: Results and Discussionmentioning
confidence: 99%
“…But for the IrP 2 (313), which is alternately terminated with P and Ir atoms, the surface provides potential sites for activating the N N bond. Hence, the HER is favorable for the (111) facet and the (313) facet is dominant for NRR (Figure 14A,B). As shown in Figure 14C, the free-energy changes revealed that the RDS is the first protonation process *N 2 + H + + e À !…”
Section: Nrrmentioning
confidence: 99%
“…Then in situ addition of benzoyl chloride and the metal (Bi, Sb and Sn) salts produces selenobenzoate complexes. [40][41][42][43] Protocol modification allows performing the reaction at room temperature (in ethanol) instead of ammonia at −70 °C. Moreover, highly pyrophoric alkali metals were replaced by a relatively mild reagent, i.e., NaBH 4 , and the reaction time was decreased from 12 hours to one hour.…”
Section: Dalton Transactions Frontiermentioning
confidence: 99%
“…51 Similar influence of primary amines have been observed towards xanthate and chalcogeno-carboxylate precursors as well: they decompose even at room temperature by primary amines. 40,41,[52][53][54][55][56] Besides catalyzing the decomposition of precursors, the surfactant may act as a reagent as well. It was reported that the decomposition of phosphorus-containing complexes yields either a metal chalcogenide or metal phosphide in the presence of trioctylphosphine (TOP).…”
Section: Selecting Suitable Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation